Adsorption and charge transfer dynamics of photovoltaic and photocatalytic dye-sensitizers - Weston, Matthew (2014)
In this thesis photovoltaic and photocatalytic water-splitting dye complexes have been studied adsorbed onto the rutile TiO2(110) surface. The photovoltaic dye-sensitizer N3 (cis-bis(isothiocyanato)bis(2,2’-bipyridyl-4,4’-dicarboxylato)-ruthenium(II)) was studied along with Ru 455 (cis-bis(2,2’-bipyridyl)-(2,2’-bipyridyl-4,4’-dicarboxylic acid) ruthenium(II)) and Ru 470 (tris(2,2’-bipyridyl-4,4’-dicarboxylic acid) ruthenium(II)) which have very similar chemical structures. Dipyrrin-based dye complexes PY1 bis(5-(4-carboxyphenyl)-4,6-dipyrrin)bis(dimethylsulfoxide)Ruthenium(II)) and PY2 (bis(5-(4-carboxyphenyl)-4,6-dipyrrin)(2,2’-bipyridine) Ruthenium(II)) were also studied which should have different bonding geometries on the TiO2 surface. A single centre water-splitting dye complex (aqua(2,2’-bipyridyl-4,4’-dicarboxylic acid)-(2,2’:6’,6”-terpyridine) Ruthenium(II)) was studied along with a chloride containing analog ((2,2’-bipyridyl-4,4’-dicarboxylic acid)-(2,2’:6’,6”-terpyridine)chloride Ruthenium(II)). The molecules studied here would have been damaged using traditional UHV deposition techniques so electrospray deposition was used to deposit intact molecules in situ for experiments in UHV. Adsorption geometries of the molecules on the TiO2 surface were investigated using experimental photoemission data supported by density functional theory (DFT) calculations. Dipyrrin-based dye complexes were found to bond with both available carboxylic acid groups to the TiO2 surface. Also the results suggest that Ru 470 is most likely to bond to the TiO2 surface with a different bonding geometry to other bipyridine-based complexes with very similar chemical structures.